The subject of romance - Brookes, L (2021)
This thesis argues that the romances written in England between 1100 and 1500 should be afforded a more central – and indeed originary – position in the history of the literary subject. It is contended that the genre of romance is intimately concerned with the depiction of individuals: that this is, in fact, in every sense the subject of romance. The introduction outlines the growing significance of the individual in fiction after the twelfth century, situating romance as the key secular genre in this development. The following chapters explore the ways in which convention, expectation, and genre intersect with the representation of identity. The thesis suggests that the depiction of subjectivity is no less central in medieval romance than it is in the modern novel; as the forerunner to the novel, romance has been both celebrated and condemned for its emphasis on plot, its repetitive storylines, and recognizable character-types of knight, and lady. By reading for these conventions, the thesis offers new readings of well-known verse and prose romances (such as Sir Gawain and the Green Knight and Sir Thomas Malory’s Le Morte Darthur) and several lesser-studied, ‘popular’ examples of the genre (including Amis and Amiloun, The Squire of Low Degree, and Le Bone Florence of Rome). As they attempt to uphold the tenets of chivalry (an ideology of constant striving and becoming), the protagonists in these texts grapple with complex and often contradictory inner lives – these are communicated to their audiences through the expression of emotion, and other ‘shorthands’ to interiority. The potential for transgression and poetic freedom is explored in a variety of romances, and their characters are recovered and expanded. The thesis concludes with a reflection on the sometimes uncomfortable positions the subjects of romance must face; unlike our own society, individuation emerges as an inevitable, but not altogether happy, state of being.